2018
DOI: 10.3389/fvets.2018.00140
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Phytotherapeutic Treatments for Different Farm Animals Under European Conditions

Abstract: The emergence and spread of antibiotic resistance is a growing global threat and has aroused a global interest in limiting antibiotic use in animal agriculture. As we are entering the post-antibiotic era, there is a growing need for identifying alternatives to antibiotics for prevention and treatment. Although phytotherapeutic remedies are available and are used in Europe, evidence of their efficacy is currently very limited but is nevertheless still necessary. A systematic review of phytotherapy used for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…It should be noted that fluctuations in peripheral blood composition were within the reference levels (Trakhtenberg et al, 1991;Abrashova et al, 2013), and the obtained data indicate a possible stimulatory effect of the drug on the organs of hematopoiesis, and the absence of toxic effect when the drug was administered intragastrically.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…It should be noted that fluctuations in peripheral blood composition were within the reference levels (Trakhtenberg et al, 1991;Abrashova et al, 2013), and the obtained data indicate a possible stimulatory effect of the drug on the organs of hematopoiesis, and the absence of toxic effect when the drug was administered intragastrically.…”
Section: Introductionsupporting
confidence: 54%
“…In the study of biochemical parameters of white rats' blood, a significant excess of all investigated parameters relative to the control group was established: total protein -by 16.5%, ALP -by 10.1%, ALT -by 12.2%, and AST -by 12.3% (Table 4), however, these indicators were also within the reference levels (Trakhtenberg et al, 1991;Abrashova et al, 2013), which on the one hand indicates the absence of toxic actions for the introduction of the drug 'Ointment for wounds' , and on the other -it stimulates the hepatobiliary system. After calculating the coefficients of the mass of the internal organs, it was found that the coefficient of lung mass was higher than the control by 9.3% (p < 0,05), and the kidney -lower by 10.1%, whereas the values of the coefficients of weight of liver, heart and spleen did not differ from those in the animals of the control group (Table 5), which confirms the absence of toxic action of the drug 'Ointment for wounds' , and indicates the development of adaptogenic processes in the rats of the experimental group.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations